HEART AND LUNG FAILURE, TRANSPLANTOLOGYLow health-related quality of life is a predictor of major adverse cardiovascular events in patients with chronic nonischemic heart failure - Szyguła-Jurkiewicz, Bożena; Zakliczyński, Michał; Owczarek, Aleksander; Partyka, Robert; Mościński, Mateusz; Pudlo, Robert; Kaczmarczyk, Marcin; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : The need to indentify patients with chronic heart failure (CHF) at a higher risk of major adverse cardiovascular events (MACEs) has become increasingly important; therefore, new parameters, such as health-related quality of life (HRQoL), are gaining ground. The aim of this study was to determine the risk factors for MACEs, with a special emphasis on HRQoL in chronic non-ischemic heart failure (NIHF) patients. Material and methods: This prospective study enrolled 271 hospitalized patients with heart failure symptoms (NYHA II and III), without neoplastic disease, diabetes, hepatic cirrhosis or chronic kidney disease, who had been receiving optimal medical treatment. In all the patients, laboratory examinations, electrocardiography, echocardiography, a 6-minute walking test, invasive right heart pressure measurements and coronary angiography were performed. HRQoL assessment was conducted with the Short-Form Health Survey (SF-36). Clinical observation commenced on admission to the hospital and lasted 3 years. Data concerning MACE incidence (death, transplantation, circulatory support, hospitalization) were obtained during outpatient visits. Results: The final analysis enrolled 202 patients, while 17 patients were lost to follow up. The MACE incidence was 42.1%. Major adverse cardiovascular events risk factors in multiple factor analysis were: alkaline phosphatase (hazard ratio [HR] = 1.01; p < 0.05); right ventricular end-diastolic diameter (HR = 1.08; p < 0.001); hsCRP (HR = 1.04; p < 0.05); and the following HRQoL indices: Bodily Pain (HR = 0.98; p < 0.05) and Mental Health (HR = 0.97; p < 0.01). Conclusions : Low values for HRQoL parameters (Bodily Pain and Mental Health), right ventricular end-diastolic diameter, serum concentration of hsCRP and alkaline phosphatase are prognostic factors in NIHF patients.